Manajemen Keuangan Pendidikan Anak Usia Dini Perspektif Wealth Management: Studi di TK Ceria Demangan Baru Yogyakarta - Raudhah Farah Dilla (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2019)
Financial management constitutes a crucial element in the performance of the entire programs and activities within an institution. This research was conducted to study financial management practices in Early Childhood Education institution namely TK Ceria Demanagn Baru Yogyakarta through the perspective of wealth management. This research is a descriptive qualitative in which data were collected through interviews and documentations. The results showed that, 1) TK Ceria Demangan Baru managed its financial resources by setting aside students’ contributions for savings funds. This will be used for purposes outside of planned financial arrangement, 2) analysed through the perspective of wealth management, the institution’s financial Management is situated in "Sd" (Student Donation) or equivalent to "E" (employees) within the Cashflow Quadrant. The actual financial management is carried out by first, conducting annual financial planning done at the beginning of each year, implementing the financial planning in all the institution’s programs and activities, recording the implementation, reporting the implementation to the foundation board, and evaluating the implementation. In addition, the implementation of the financial management is carried out by considering the principles of transparency, public accountability, effectiveness and efficiency. Meanwhile, institutional fund obtained merely from students’ contribution reduces the quantity of institutional financial income.